KONVERSI BUDIDAYA UDANG VANAMEI DARI SISTEM TRADISIONAL MENUJU SISTEM INTENSIF DI KELURAHAN AIR JUKUNG, KECAMATAN BELINYU, KABUPATEN BANGKA - Priyambada, Agung; Nugraha , Mohammad Agung; Ambalika , Indra; Hudatwi, Mualimah (Universitas Mataram, 2024)
The Vannamei shrimp cultivation system used by the Tambak Atok Asri group employs traditional cultivation methods. However, traditional pond cultivation currently faces several challenges. Some of these challenges include suboptimal productivity of the cultivation, shrimp growth that does not meet the target and declining shrimp health due to decreasing water quality in traditional ponds. This community engagement activity aims to convert traditional system shrimp cultivation technology to an intensive system to increase the productivity of harvested shrimp in the shrimp ponds of Air Jukung Village. The method of this activity is actively participatory with the involvement of cultivator groups starting from planning, implementation, and evaluation. The result of the activity is that the conversion of the traditional shrimp cultivation system to an intensive system can increase crop productivity and shrimp growth according to the target. The conclusion from this service is that partners have the knowledge and skills to convert traditional system shrimp cultivation technology to an intensive system which can increase shrimp productivity.